2022
DOI: 10.1037/aap0000257
|View full text |Cite
|
Sign up to set email alerts
|

Colonial mentality and psychological flexibility among Filipinx Americans.

Abstract: While the concept of colonial mentality (CM; David & Okazaki, 2006a) has been well examined in the literature, little is understood about addressing CM in a clinical setting. The aim of this study is to examine a relationship between CM and psychological flexibility (PF; Hayes et al., 2013), with the hope of establishing acceptance and commitment therapy (ACT) as a clinically relevant theoretical orientation for addressing CM. Filipinx American participants (N = 856) completed online questionnaires regarding C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
(100 reference statements)
1
7
0
Order By: Relevance
“…It is a unique set of attitudes that involve denigration of one’s own culture while appreciating or valuing Westernized culture. Colonial mentality has been found among individuals who inhabit countries that were once colonized (David et al, 2017; Estrellado et al, 2022). Within the Filipinx American culture, colonial mentality unfolds as internalizing experiences of racism and oppression by condemning one’s own culture and valuing Western culture, ideals, and lifestyle (David & Okazaki, 2006; Estrellado et al, 2022).…”
Section: Colonial History In the Philippinesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a unique set of attitudes that involve denigration of one’s own culture while appreciating or valuing Westernized culture. Colonial mentality has been found among individuals who inhabit countries that were once colonized (David et al, 2017; Estrellado et al, 2022). Within the Filipinx American culture, colonial mentality unfolds as internalizing experiences of racism and oppression by condemning one’s own culture and valuing Western culture, ideals, and lifestyle (David & Okazaki, 2006; Estrellado et al, 2022).…”
Section: Colonial History In the Philippinesmentioning
confidence: 99%
“…It is a unique set of attitudes that involve denigration of one's own culture while appreciating or valuing Westernized culture. Colonial mentality has been found among individuals who inhabit countries that were once colonized (David et al, 2017;Estrellado et al, 2022).…”
Section: Colonial Mentalitymentioning
confidence: 99%
See 1 more Smart Citation
“…This landmark issue includes articles that demonstrate how cultural connectedness—or loss of such connectedness—is important for FA mental health and well-being (Coffee et al, 2021; Cotas-Girard et al, 2021). Other articles explore the psychological damages of historical and contemporary experiences of oppression (Estrellado et al, 2021; Nadal et al, 2021), including those most recently revealed and amplified by the coronavirus disease (COVID-19) pandemic (Arañez-Litam & Oh, 2021). Some researchers attempted to better understand one of the more consistent findings in Asian American psychology—that as low as the mental health help-seeking rate is for Asian Americans, FAs seek professional psychological help at an even lower rate (Gong et al, 2003; Tanaka-Konayagi, 2001; Ying & Hu, 1994)—by investigating other factors that might influence FA mental health help-seeking (Alviar & del Prado, 2021; Tuazon & Clemente, 2021).…”
Section: Celebrating Filipina/x/o American Psychologymentioning
confidence: 99%
“…We have many strengths as a community, and we can use FA Psychology to explicitly recognize them and make them a more prominent part of the community narrative. One example of this is Estrellado et al (2021) article in this special issue, where one implication of their work is the possibility that psychological flexibility among FAs may operate as a protective factor against the negative psychological effects of colonial mentality. Similarly, Arañez-Litam and Oh (2021) in this special issue also sought to identify FA coping strategies that can buffer the negative mental health effects of racism.…”
Section: Four Guiding Principles For Filipina/x/o American Psychologymentioning
confidence: 99%